The Sub-Criteria for Evacuation-Based Pedestrian Route Design Parameters - Agenta, Veiga Mustika; Rifwan, Fitra; Yosritzal, Yosritzal; Purnawan, Purnawan; Yossyafra, Yossyafra (Universitas Negeri Padang, 2023)
Indonesia, surrounded by three major tectonic plates—the Indo-Australian plate, the Pacific plate, and the Eurasian plate—faces a relatively high disaster risk. The city of Padang in West Sumatra, located on the western side of Sumatra Island and in proximity to tectonic plates, is particularly susceptible to earthquakes and tsunamis. To mitigate disaster risk, Padang requires evacuation-focused road infrastructure, including pedestrian paths. This study aims to assess the validity of sub-criteria parameters for creating pedestrian evacuation routes in Padang. It employs quantitative descriptive research methods, utilizing Aiken's V and Cronbach Alpha. The study involved distributing validation forms to five experts, comprising two Civil Engineering lecturers and three members of Padang City's BPBD (Regional Disaster Management Agency) specializing in Planning and Preparedness. The participants' responses, recorded through the forms, served as data for analyzing and identifying sub-criteria for evacuation-oriented pedestrian route design parameters. The study's findings reveal that one sub-criteria—Safety Fence from the Amenities parameter with a value of V = 0.7—is invalid.